The Impact of NFTArt on The Art Market: Yestarday, Today and Future Perspectives - Aydogan, Derya (ATATURK UNIV, 2024)
The individual characteristic of an art work is its uniqueness. Digital art has, in the sense, deconstructed this basic feature in terms of unlimited copying and distribution and brought about a controversial process. With its registrability feature NFT (non-fungible token has in a sense re-delivered the uniqueness and originality which are characteristics specific to classical art and a matter of debate in digital art. NFT has occupied the agenda in many areas especially in recent years and has come to the fore in the art environment. Over time it is seen that not only those who produce NFT art, but also the structures that dominate art have approached this issue and organized events where they produced a number of projects. However there is a possibility that the interest created on any issue in the market may be manipulative. It should be taken into consideration that manipulation is strong in the art market. Looking at the survey results and findings of various analysis companies around the world can be guiding in terms of drawing a more realistic picture. Therefore, in this study the data obtained from the statistics made by various analysis companies on NFT technolology in the last three years were examined (2021-2023). NFT marketplaces and NFT exhibitions in pyhsical, virtual and hybrid environments were researched and examples were exhibited. The correlation was evaluated by looking at the relationship between the breakthroughts in NFT art and the statistics that give more concrete results.
Keywords: Art market; registration; NFT art; NFT exhibition; NFT market; Art